ADAMTS13 protease or lack of von Willebrand factor protects irradiation and melanoma‐induced thrombotic microangiopathy in zebrafish. (7th August 2022) - Zheng, Liang; Cao, Liyun; Zheng, X. Long
Abstract: Background: Severe deficiency of plasma ADAMTS13 activity may result in potentially fatal thrombotic thrombocytopenic purpura and relative deficiency of plasma ADAMTS13 activity may be associated with adverse outcomes of certain malignancies. Here, we report the role of ADAMTS13 or lack of von Willebrand factor (VWF) in reducing irradiation and melanoma‐induced thrombotic microangiopathy (TMA) and mortality in zebrafish. Methods: Zebrafish melanoma cell line (ZMEL) was injected subcutaneously into wild‐type ( wt ), adamts13 −/− ( a13 −/− ), von Willebrand factor ( vwf −/− ), and a13 −/− vwf −/− zebrafish following total body irradiation; the tumor growth, its gene expression pattern, the resulting thrombocytopenia, and the mortality were determined . Results: Total body irradiation at 30 Gy alone resulted in a transient thrombocytopenia in both wt and a13 − /− zebrafish. However, thrombocytopenia occurred earlier and more profound in a13 −/− than in wt zebrafish, which was resolved 2 weeks following irradiation alone. An inoculation of ZMEL following the irradiation resulted in more severe and persistent thrombocytopenia, as well as earlier death in a13 −/− than in wt zebrafish. The vwf −/− or a13 −/− vwf −/− zebrafish were protected from developing severe thrombocytopenia following the same maneuvers. RNA‐sequencing revealed significant differentially expressed genes associated with oxidation–reduction, metabolism, lipid, fatty acid and cholesterol metabolic processes, steroid synthesis, and phospholipid efflux in the melanoma explanted from a13 −/− zebrafish compared with that from the wt controls. Conclusions: Our results indicated that plasma ADAMTS13 or lack of VWF may offer a significant protection against the development of irradiation‐ and/or melanoma‐induced TMA. Such a microenvironment may directly affect melanoma cell phenotypes via alternation in the oxidation–reduction and lipid metabolic pathways.